A self-templating scheme for the synthesis of NiCo2Se4 and BiSe hollow microspheres for high-energy density asymmetric supercapacitors. Issue 11 (1st March 2022) - Xia, Jingjing; Zhang, Liuming; Xuan, Shouguo; Ni, Yonghong; Zhang, Li
Abstract : Porous hollow structures of electrode materials can enlarge the surface area in contact with electrolytes, accelerating the transport of ions and electrons during redox reactions to enhance the electrochemical performance of the electrode materials. Abstract : Porous hollow structures of electrode materials can enlarge the surface area in contact with electrolytes, accelerating the transport of ions and electrons during redox reactions to enhance the electrochemical performance of the electrode materials. Herein, this work presents a facile method to synthesize NiCo2 Se4 hollow microspheres (NiCo2 Se4 HMSs) and BiSe hollow microspheres (BiSe HMSs) based on a self-template and selenide strategy. NiCo2 Se4 HMSs deliver a high specific capacitance of 262.0 mA h g −1 (1874.6 F g −1 ) at a current density of 1 A g −1 and good rate capability (74.9% capacitance retention at 20 A g −1 ), which is superior to many Ni/Co-based electrode materials. Meanwhile, BiSe HMSs show an amazing capacitance of 360 mA h g −1 (1293 F g −1 ) at 1 A g −1 and excellent rate capability (62.6% capacitance retention at 40 A g −1 ). On account of the unique chemical composition and structural features, the assembled NiCo2 Se4 HMSs//BiSe HMSs asymmetric supercapacitors (ASCs) exhibit high energy density (76.73 W h kg −1 at 1.79 kW kg −1 ) and good capacitance retention (93.4%) after 3000 cycles. This study suggests that these unique selenide structures have potential applications in fabricating high-performance ASCs, which is expected to be one of highly prospective energy storage devices.